Career preferences of the second and fourth year students of the Hadji Butu School of Arts and Trades in relation to the manpower needs of Jolo - Chang, Precilla C. Diansuy 1943-
This study sought to identify the inventories and expressed career preferences of the second year high school students of the Hadji Butu School of Arts and Trades and to relate these preferences to the manpower needs of Jolo. It used the descriptive survey for the collection of data to which the critical ratio and chi square test were applied for statistical analysis. The sample consisted of 293 and 221 second year and fourth year students. Results revealed that boys showed high interest in the persuasive and mechanical areas and low interest in the computational and scientific areas. Females showed high interest in personal service and low in persuasive and literary areas. The inventoried and expressed interest of the subjects are inconsistent with each other. Girls appear to be more homogeneous in their interest patterns than boys. The author concluded that there is a need to make the studentry more aware of the manpower needs of Jolo as well as of the region.